Implementación de biorremediación de lodos mediante larvas de mosca soldado en cámaras anaeróbicas de PTAR vista al parque - Portero Ruiz, Andrés Danilo (2024)
The "Vista al Parque-Samborondón" wastewater treatment plant has been in operation for 25 years with the purpose of treating wastewater from 400 homes that make up the urbanization. The WWTP has a treatment capacity of 320,000 liters per day, which is equivalent to 3.70 liters per second. Over time, organic waste has accumulated in a chamber with a surface area of 5.4 meters by 3.60 meters with a depth of 4 meters, with a capacity for 421.44 tons, from which approximately 316 tons of sludge annually using a hydrocleaner truck, which represents 75% of the chamber capacity. The present research focuses on sludge purification through the bioremediation method using soldier fly larvae (Hermetia illucens). The main objective is to reduce the organic material up to 50% to improve the quality of the treatment, generate maintenance savings by taking advantage of the resulting material, avoiding taking it to landfills that contribute to a pollutant for the environment since the soil loses minerals with the presence of nitrogen giving way to leachates and gas emissions that can affect the quality of groundwater or the health of the soil.